Solar Electric Bicycle Body Modeling and Simulation - Zhikun Wang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
A new solar electric bicycle design and study were carried out on in this paper. Application of CAD technology to establish three-dimension geometric model, using the kinetic analysis on the frame and other parts for numerical simulation and static strength analysis for the vehicle model design, virtual assembly, complete frame dynamics analysis and vibration analysis, with considering other factors, first on the frame structure improvement, second on security of design calculation analysis and comparison, finally get the ideal body design. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.3410